On the convergence of the sums of independent, integer-valued processes - Szász, D. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Д. Саас. О сходимости сумм независимых целозначных процессовD. Saasas. Apie nepriklausomų, įgyjančių sveikas reikšmes, procesų sumų konvergavimą